Lung Separation in the Morbidly Obese Patient - Javier H. Campos; Kenichi Ueda (Anesthesiology Research and Practice)
Lung separation techniques in the morbidly obese patient undergoing thoracic or esophageal surgery may be at risk of complications during airway management. Access to the airway in the obese patient can be a challenge because they have altered airway anatomy, including a short and redundant neck, limited neck extension and accumulation of fat deposition in the pharyngeal wall contributing to difficult laryngoscopy. Securing the airway is the first priority in these patients followed by appropriate techniques for lung separation with the use of a single-lumen endotracheal tube and a bronchial blocker or another alternative is with the use of a double-lumen endotracheal tube. This review is focused on the use of lung isolation devices in the obese patient. The recommendations are based upon scientific evidence, case reports or personal experience. Fiberoptic bronchoscopy must be used to place and confirm proper placement of a single-lumen endotracheal tube, bronchial blocker or double-lumen endotracheal tube.